Analisis Konversi Lahan Perkebunan Karet Rakyat Menjadi Pertanian Ubi Kayu Terhadap Pendapatan Petani Desa Cempedak Lobang Kecamatan Sei Rampah Kabupaten Serdang Bedagai - Siregar, Agus Saputra; Kuswardani, Retna Astuti; Rahmanta, Rahmanta (AGRISAINS: Jurnal Ilmiah Magister Agribisnis, 2021)
This study aims to determine the difference in income between rubber farmers and cassava farmers. To determine the difference in farming efficiency between rubber farmers and cassava farmers, to determine whether there are marketing prospects for cassava versus rubber. This study uses primary data data obtained by using a list of questions that have been prepared. The results showed that the income in rubber farming was Rp. 33,907,379.20 per hectare, while the income from cassava farming is Rp. 39,725,568.13 per hectare. Income from rubber farming is lower than that of cassava farming, with a difference of Rp. 5,818,188.93. The average difference test shows that there is a significant difference between the income of rubber farming and the income of cassava farming, where the income of cassava farming is greater. The R / C value for rubber farming was 5.16, while the R / C value for cassava farming was 8.47, with a difference in feasibility of 3.31. The results of the average difference test on the R / C value show that there is a significant difference between the feasibility of rubber farming and the feasibility of cassava farming, where cassava farming is more efficient. Cassava marketing in the future has a pretty good prospect, because the demand for cassava and its processed products tends to increase, there are many companies that can accommodate cassava products, and the price level of cassava tends to increase every year.